Analysis of the Effectiveness of the Family Hope Program (PKH) in Reducing Poverty in Makassar City - Mario Mario; Bahrul Hamsal (International Journal of Social Science and Humanity, 2025)
Poverty in Makassar City is a multidimensional problem that not only covers economic, but also social and cultural aspects. The Family Hope Program (PKH) was initiated as a conditional social assistance intervention to ease the burden on poor families through increased access to education and health. This study aims to analyze the effectiveness of PKH in improving the welfare of poor families in Makassar, identify socio-cultural factors that affect the success of the program, and explore the obstacles faced by beneficiaries and social companions. A descriptive qualitative approach was used with research subjects including 10 beneficiary families and 3 social companions. Data were collected through in-depth interviews, participatory observations, and document studies, then analyzed thematically using an inductive approach. The results of the study show that PKH contributes significantly to reducing the economic burden of families, especially in meeting children's educational and health needs. The success of the program is influenced by the role of social companions who are communicative and adaptive to the local cultural context. However, complicated bureaucracy, limited access to public services, inaccurate recipient data, and social stigma are the main obstacles that hinder the effectiveness of the program. Awareness and active participation of beneficiaries in carrying out program obligations are also the key to success. The research concludes that PKH needs to be supported by simplifying administrative procedures, strengthening the capacity of companions, and culturally sensitive approaches to increase the impact of programs in poverty alleviation in Makassar City.